2017
DOI: 10.4236/oje.2017.713046
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Water Hyacinth (<i>Eichhornia crassipes</i>) Is Associated with Decline in Macrophyte Biodiversity in an Ethiopian Rift-Valley Lake—Abaya

Abstract: Macrophytes play critical ecological role in inland water bodies, especially in shallow systems. Water hyacinth (Eichhornia crassipes) is an invasive plant species introduced to Ethiopian water bodies around the mid 20 th century with recently exacerbated devastating ecological and economic consequences. Here we report the impact of the invasive plant species on macrophyte species assemblage and biodiversity in Lake Abaya, southwestern Ethiopia. We compared four sites in Lake Abaya, two hyacinth infested and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…crassipes and P . stratiotes caused great harm to the local biodiversity of aquatic plants, phytoplankton and aquatic animals (Coetzee et al, 2014; Mengistu et al, 2017; Thamaga & Dube, 2018; Wang et al, 2016). In this study, we found that the abundance of epiphytic algae on the native macrophyte species ( H .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…crassipes and P . stratiotes caused great harm to the local biodiversity of aquatic plants, phytoplankton and aquatic animals (Coetzee et al, 2014; Mengistu et al, 2017; Thamaga & Dube, 2018; Wang et al, 2016). In this study, we found that the abundance of epiphytic algae on the native macrophyte species ( H .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the invasion of E. crassipes and P. stratiotes caused great harm to the local biodiversity of aquatic plants, phytoplankton and aquatic animals (Coetzee et al, 2014;Mengistu et al, 2017;Thamaga & Dube, 2018;Wang et al, 2016). In this study, we found that the abundance of epiphytic algae on the native macrophyte species (H. dubia) was greater than that on the invasive species (E. crassipes and P. stratiotes) in both the field investigation and mesocosm experiment (Figure 2), which suggested that invasive free-floating macrophytes might have a stronger inhibitory effect than native free-floating macrophytes on epiphytic algae.…”
Section: Invasive Free-floating Macrophytes Had a Stronger Inhibitory...mentioning
confidence: 99%
See 1 more Smart Citation
“…The highly reproductive nature of water hyacinth poses a great threat to biodiversity as the weed easily outcompetes other species. Mengistu et al [ 102 ] compared the impact of water hyacinth on the assemblage of macrophyte species in infested and noninfested parts of Lake Abaya, Ethiopia. It was reported that water hyacinth affects the composition of macrophytes, their abundance, and diversity so much so that in extreme instances, the community of the macrophytes shrank into single flora.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it emerged to be among the ten top ecologically risky aquatic flowers in the country. It has inflicted adverse impact on social, economic and livelihood condition of the people and development projects in the Rift Valley Lakes Region (Mengistu, Unbushe & Abebe, 2017).…”
Section: Introductionmentioning
confidence: 99%